Analysis of the Influence of Work-Life Balance Policy on Employee Performance in Service Companies - Helmi Saputra (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
This study investigates the effect of work-life balance on personnel performance in Service companies. The research method is qualitative method, sampling through observation and interview method, data analysis technique is multiple linear regression analysis. This research also shows the existence of concurrent influence, which indicates the existence of work- life balance variables that have a significant concurrent influence on employee performance